2009
DOI: 10.1038/icb.2008.83
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T cells in the thymus: have they just lost their way or do they do something?

Abstract: In young adult mice, the thymus produces about a million newly formed T cells every day that colonize peripheral lymphoid tissues. Mostly regarded as a primary lymphoid organ only, the relationship between the thymus and peripheral lymphoid organs is considered unidirectional. However, this perception has been challenged by reports showing that peripheral lymphocytes, mostly T cells, can migrate back into the thymus. The presence of recirculating T cells in the thymus is rather incongruous and raises the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
(158 reference statements)
1
16
0
1
Order By: Relevance
“…Within the thymus we detected this T cell population within the mature, CD4 or CD8 single positive medullary T cell population. This might indicate that these cells originate from the thymus, although also evidence for a migration from mature T cells back to the thymic medulla has been reported (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Within the thymus we detected this T cell population within the mature, CD4 or CD8 single positive medullary T cell population. This might indicate that these cells originate from the thymus, although also evidence for a migration from mature T cells back to the thymic medulla has been reported (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Once homing to the thymus, they are predominantly localized in the medulla and remain there for prolonged periods 33 . It is estimated that the thymus of an adult mouse can accommodate about 10 5 recirculating peripheral T cells 3537 . Despite the relatively constant number, the proportion of such cells increases dramatically with age, accounting for more than 20% of single positive (SP) thymocytes in mice over 1 year of age 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Is the presence of peripheral T cells in the thymus merely an epiphenomenon or are they destined to fulfill some relevant physiological functions ? Despite controversy, evidence is emerging that these cells may participate in the shaping of the T cell repertoire by delivering self antigens into the thymus 35, 36, 3840 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several reports showed that back-migration can occur, and mature peripheral T cells may re-enter the thymus (2)(3)(4)(5). Apparently, ∼10…”
mentioning
confidence: 99%
“…5 mature T cells from the periphery can be accommodated in a specific thymic niche (3) and mainly localize to the medulla (6). Multiple possible functions have been assigned to these cells, such as maintenance of medullary thymic epithelial cells (mTECs) or direct mediation of thymocyte selection in certain experimental settings (7)(8)(9)(10).…”
mentioning
confidence: 99%